Developmental decisions in Dictyostelium discoideum. - Strmecki, L; Greene, D; Pears, C (2005)
Dictyostelium discoideum is an excellent system in which to study developmental decisions. Synchronous development is triggered by starvation and rapidly generates a limited number of cell types. Genetic and image analyses have revealed the elegant intricacies associated with this simple development system. Key signaling pathways identified as regulating cell fate decisions are likely to be conserved with metazoa and are providing insight into differentiation decisions under circumstances where considerable cell movement takes place during development.